SPIRITUALITAS KOMUNAL NUSANTARA: MODEL KONSELING PASTORAL BERBASIS GOTONG ROYONG - Tuerah, Joshua; Gagola, Patricia; Salenda, Richi; Lintjewas, Francien (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2025)
In the era of globalization, rapid social change has impacted the lives of Indonesians. Societal values ​​have shifted from communal values ​​to a more individualistic lifestyle as a result of modernization and advances in information technology. As a result, many people feel a loss of meaning in life, alienated from their communities, and experience increasingly complex mental and spiritual stress. Lestari and Gunawan emphasize the importance of a contextual pastoral approach: "Contextual pastoral counseling must be able to bridge faith values ​​with local culture in order to address the real needs of the congregation. Given the importance of this approach, this study aims to explore the communal spirituality of the Indonesian archipelago, particularly the value of mutual cooperation, as a foundation for developing a more contextual and participatory pastoral counseling model. This opens up new space for the church to develop pastoral methods that are closer to the roots of community life and encourage congregations to function as healers for others. From this discussion, it becomes increasingly clear that developing a pastoral counseling model based on mutual cooperation is a crucial step in addressing the need for contextual, relevant, and participatory church services.